RESPON MALAYSIA DAN SINGAPURA DALAM MENGHADAPI KABUT ASAP YANG TERJADI DI INDONESIA TAHUN 2011-2015 - Faradiba, Faradiba (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The objectives of this research are to analyze the neighboring countries’ response, which are Malaysia and Singapore, in facing the effect of forest fires smoke in Indonesia from 2011 until 2015 and to analyze the Indonesian Government's feedback when getting the response from both countries. This research uses the green political theory and securitization theory to analyze the research problems. The periodization of this research is limited from 2011 until 2015 in which forest and land fires actually occur almost every year starting from the El Nino phenomenon in 1997/1998. This research is qualitative research. The result of this research indicates that even though forest fires happen every year in Indonesia but forest fires smoke does not always pass across Malaysia and Singapore. Therefore, Malaysia and Singapore do not always send the letter of complaint to Indonesia oh the forest fires smoke pollution which might disturb the activities of Malaysian and Singaporean people, particularly in the sector of health, tourism, transportation, economy and education.